Preparation method and application of boron-nitrogen co-doped porous carbon material
Through boron and nitrogen co-doping technology, porous carbon materials with excellent specific surface area, strength and electrochemical performance were prepared, which solved the problem of poor circulation performance of existing materials in lithium/sodium ion batteries and achieved better electricity Chemical properties and expansion constraint effects.
Patent Information
- Application Number
- CN202411413529.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Existing porous carbon materials exhibit lower specific surface area, pore volume and strength in lithium/sodium ion batteries, resulting in poor electrochemical cycling performance.
Using boron and nitrogen co-doping technology, Schiff base polymerization was carried out through pyridine formaldehyde intermediate and 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid, and epoxy groups were introduced. The group is hydrolyzed by concentrated sulfuric acid to form a polyhydroxy structure, and then complex with boric acid to uniformly adsorb boric acid, and then prepare boron nitrogen co-doped porous carbon material through high-temperature carbonization.
The specific surface area and pore volume of porous carbon materials are significantly improved, their strength and electrochemical properties are enhanced, and the circulation performance and expansion constraint effect of lithium/sodium ion batteries are improved.
Smart Images

Figure SMS_2 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous carbon materials, and in particular to a preparation method and application of a boron-nitrogen co-doped porous carbon material. Background Art
[0002] Porous carbon materials are widely used in the support of active materials for lithium / sodium ion batteries, catalysts, gas separation and storage due to their high specific surface area, good chemical stability and excellent electrochemical performance. The precursors for preparing porous carbon mainly include natural biomass, macromolecular polymers, etc. Among them, microporous polymers have a large number of pore structures and rigid skeletons, and are one of the precursors for preparing high-performance porous carbon materials.
[0003] Heteroatom doping modification of porous carbon materials can improve their electrochemical properties and pore structure, and expand the practical application of porous carbon in lithium / sodium ion batteries and other aspects. Patent CN115140728B discloses that melamine, ammonium borate, tetraethyl orthosilicate, hydrochloric acid, etc. are used as raw materials to obtain a colloidal precursor solution; after being converted into composite particles, high-temperature carbonization and ball milling treatment are performed, and the boron and nitrogen doped lithium ion battery negative electrode materials obtained show stable electrochemical cycle stability and rate performance. However, the carbonized product does not show a higher specific surface area and pore volume, as well as higher strength. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a method for preparing a boron-nitrogen co-doped porous carbon material with high specific surface area, high strength and excellent electrochemical performance. When used as a carrier of active material for lithium / sodium ion battery electrodes, better expansion constraint effect can be obtained, thereby improving battery cycle performance.
[0005] The technical solution of the present invention is: a method for preparing a boron-nitrogen co-doped porous carbon material:
[0006] Step (1), nitrogen is introduced into the flask, 1,4-dioxane, pyridine carboxaldehyde intermediate, 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid (structural formula: , CAA number is 2130-56-5), after stirring and dissolving, add acetic acid solution dropwise, heat to 100-110°C, condense and reflux for 36-48h, centrifuge, wash with water and ethanol, then extract in tetrahydrofuran with a Soxhlet extractor, and dry to obtain a carboxyl microporous polymer.
[0007] Step (2), adding N,N-dimethylformamide, carboxyl microporous polymer, propylene oxide, N,N-dicyclohexylcarbodiimide, and 4-dimethylaminopyridine into a flask, carrying out esterification reaction, centrifuging, washing with water and ethanol, and then extracting in dichloromethane using a Soxhlet extractor, drying, adding the product to a sulfuric acid solution, carrying out a hydrolysis reaction, centrifuging, washing with water, and drying to obtain a hydroxyl microporous polymer.
[0008] Step (3), add boric acid aqueous solution and hydroxyl microporous polymer to a flask, stir and adsorb at 20-35°C for 3-6 hours, filter and wash with water, add the product to a tubular furnace after drying, introduce nitrogen, heat to 800-900°C, keep warm and calcine for 2-4 hours, cool, and obtain a boron-nitrogen co-doped porous carbon material.
[0009] Furthermore, in step (1), the molar ratio of the pyridine carboxaldehyde intermediate to 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid is 1:(1.3-1.7).
[0010] Furthermore, the mass fraction of the acetic acid solution in step (1) is ≥ 80%.
[0011] Furthermore, in step (2), the mass ratio of the carboxyl microporous polymer, propylene oxide, N,N-dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1:(0.4-0.7):(1.1-2.6):(0.12-0.3).
[0012] Furthermore, in step (2), the esterification reaction is carried out at 20-35°C for 18-24 hours; and the hydrolysis reaction is carried out at 60-75°C for 8-12 hours.
[0013] Furthermore, the mass fraction of the sulfuric acid solution in step (2) is 1-1.6%.
[0014] Furthermore, in step (3), the ratio of the boric acid aqueous solution to the hydroxyl microporous polymer is 1L:(5-20)g; and the mass fraction of the boric acid aqueous solution is 0.06-0.25%.
[0015] Furthermore, the preparation method of the pyridine carboxaldehyde intermediate is as follows: nitrogen is introduced into a flask, toluene solvent is added in a volume ratio of (3-4):1, ethanol blocking solvent is added, 5-bromo-2-pyridine carboxaldehyde (CAS No. 31181-90-5) in a molar ratio of (3.3-3.6):1:(0.09-0.12), 1,3,5-benzenetriboric acid tripinacol ester (CAS No. 365564-05-2), tetrakis(triphenylphosphine)palladium is added dropwise with a molar concentration of 1.5-2 mol / L potassium carbonate aqueous solution, heated to 80-100°C, reacted for 18-24h, rotary evaporated, added with dichloromethane for extraction, the organic phase was dried with anhydrous sodium sulfate, filtered, rotary evaporated, and the product was recrystallized in dichloromethane to obtain the pyridine carboxaldehyde intermediate. The reaction formula is as follows
[0016]
[0017] Furthermore, the application of boron-nitrogen co-doped porous carbon materials in the negative electrode of lithium-ion batteries.
[0018] Technical effect: The present invention couples 5-bromo-2-pyridinecarboxaldehyde and 1,3,5-benzenetriboric acid tripinacol ester, and the obtained pyridinecarboxaldehyde intermediate undergoes Schiff base polymerization with 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid to obtain a carboxyl microporous polymer, which is further esterified with glycidol to introduce epoxy groups ( ) is hydrolyzed by concentrated sulfuric acid to generate a polyhydroxy structure ( ), thereby obtaining a hydroxyl microporous polymer. Its polyhydroxy structure can react with boric acid to form a complex ( ), thereby uniformly adsorbing a large amount of boric acid into the microporous polymer. After high-temperature carbonization, pyridine ring is used as the nitrogen source and boric acid is used as the boron source to obtain boron-nitrogen co-doped porous carbon material.
[0019] The specific surface area of the boron-nitrogen co-doped porous carbon material of the present invention reaches 1042.7-1506.5 m 2 / g, and the total pore volume reaches 0.535-0.883 cm 3 / g. Showing huge specific surface area and pore volume.
[0020] The boron-nitrogen co-doped porous carbon material of the present invention can be used as an active material for the negative electrode of a lithium-ion battery. A large amount of active pyridinic nitrogen, graphitic nitrogen and other nitrogen-containing active groups are uniformly distributed in the porous carbon matrix, which can improve the electrical conductivity of the porous carbon group and the electrochemical lithium storage site. At the same time, boron doping generates active boron substances such as BC2O, BCO2, and BC3, generates hole-type charge carriers, forms defects, increases active sites, and reduces the energy barrier of lithium ion diffusion. In addition, the pore structure is rich, which can improve the transmission channel, promote the extraction and embedding of lithium ions, and improve the ion transmission rate. Under different current densities, it has a high charge and discharge specific capacity, coulomb efficiency and rate performance. And after multiple cycles, it still has a high discharge specific capacity, and the cycle stability performance is very good, thereby showing excellent electrochemical performance.
[0021] The boron-nitrogen co-doped porous carbon material of the present invention can also be used as a carrier of active substances such as phosphorus and silicon to obtain phosphorus-carbon composite negative electrode materials and phosphorus-silicon composite negative electrode materials for sodium ion batteries, both of which show good electrochemical properties. DETAILED DESCRIPTION
[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0023] Example 1
[0024] Nitrogen was introduced into the flask, and 240 mL of toluene solvent, 80 mL of ethanol as a solvent, 36 mmol of 5-bromo-2-pyridinecarboxaldehyde, 10 mmol of 1,3,5-benzenetriboric acid tripinacol ester, and 0.9 mmol of tetrakis(triphenylphosphine)palladium were added in a volume ratio. 40 mL of 1.5 mol / L potassium carbonate aqueous solution was added dropwise, and the mixture was heated to 100 ° C. The reaction was carried out for 18 hours, and the mixture was rotary evaporated. Dichloromethane was added for extraction. The organic phase was dried over anhydrous sodium sulfate, filtered, and rotary evaporated. The product was recrystallized in dichloromethane to obtain a pyridinecarboxaldehyde intermediate.
[0025] Example 2
[0026] Nitrogen was introduced into the flask, and 320 mL of toluene solvent, 80 mL of ethanol as a solvent, 33 mmol of 5-bromo-2-pyridinecarboxaldehyde, 10 mmol of 1,3,5-benzenetriboric acid tripinacol ester, and 1.2 mmol of tetrakis(triphenylphosphine)palladium were added. 30 mL of 2 mol / L potassium carbonate aqueous solution was added dropwise, and the mixture was heated to 80 ° C. The reaction was carried out for 24 h, and the mixture was rotary evaporated. Dichloromethane was added for extraction. The organic phase was dried over anhydrous sodium sulfate, filtered, and rotary evaporated. The product was recrystallized in dichloromethane to obtain a pyridinecarboxaldehyde intermediate.
[0027] Example 3
[0028] Step (1), nitrogen is introduced into a flask, 500 mL of 1,4-dioxane, 30 mmol of pyridine carboxaldehyde intermediate (prepared according to the method of Example 1), and 46 mmol of 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid are added, and after stirring and dissolving, 20 mL of 95% acetic acid solution is added dropwise, and the mixture is heated to 110° C., condensed and refluxed for reaction for 36 hours, centrifuged, washed with water and ethanol, and then extracted in tetrahydrofuran using a Soxhlet extractor, and dried to obtain a carboxyl microporous polymer.
[0029] Step (2), add 400 mL of N,N-dimethylformamide, 20 g of carboxyl microporous polymer, 14 g of propylene oxide, 52 g of N,N-dicyclohexylcarbodiimide, and 6 g of 4-dimethylaminopyridine into a flask, carry out esterification reaction at 20° C. for 18 hours, centrifuge, wash with water and ethanol, then extract in dichloromethane with a Soxhlet extractor, dry, add the product to a 1.6% sulfuric acid solution, carry out hydrolysis reaction at 75° C. for 8 hours, centrifuge, wash with water, and dry to obtain a hydroxyl microporous polymer.
[0030] Step (3), add 1L of 0.06% boric acid aqueous solution and 5g of hydroxyl microporous polymer into a flask, stir and adsorb at 20°C for 4h, filter and wash with water, add the product into a tubular furnace after drying, introduce nitrogen, heat to 800°C, keep warm and calcine for 4h, cool, and obtain a boron-nitrogen co-doped porous carbon material.
[0031] Example 4
[0032] Step (1), nitrogen is introduced into a flask, 500 mL of 1,4-dioxane, 30 mmol of pyridine carboxaldehyde intermediate (prepared according to the method of Example 1), and 51 mmol of 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid are added, and after stirring and dissolving, 20 mL of 95% acetic acid solution is added dropwise, and the mixture is heated to 100° C., condensed and refluxed for reaction for 48 hours, centrifuged, washed with water and ethanol, and then extracted in tetrahydrofuran using a Soxhlet extractor, and dried to obtain a carboxyl microporous polymer.
[0033] Step (2), add 300 mL of N,N-dimethylformamide, 20 g of carboxyl microporous polymer, 8 g of propylene oxide, 22 g of N,N-dicyclohexylcarbodiimide, and 2.4 g of 4-dimethylaminopyridine into a flask, carry out esterification reaction at 25° C. for 24 hours, centrifuge, wash with water and ethanol, then extract in dichloromethane with a Soxhlet extractor, dry, add the product to a 1% sulfuric acid solution, carry out hydrolysis reaction at 60° C. for 12 hours, centrifuge, wash with water, and dry to obtain a hydroxyl microporous polymer.
[0034] Step (3), add 1L of 0.15% by mass boric acid aqueous solution and 12g of hydroxyl microporous polymer into a flask, stir and adsorb at 35°C for 3h, filter and wash with water, add the product into a tubular furnace after drying, introduce nitrogen, heat to 900°C, keep warm and calcine for 2h, and cool to obtain a boron-nitrogen co-doped porous carbon material.
[0035] Example 5
[0036] Step (1), nitrogen is introduced into a flask, 400 mL of 1,4-dioxane, 30 mmol of pyridine carboxaldehyde intermediate (prepared according to the method of Example 1), and 39 mmol of 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid are added, and after stirring and dissolving, 25 mL of 95% acetic acid solution is added dropwise, and the mixture is heated to 110° C., condensed and refluxed for reaction for 36 hours, centrifuged, washed with water and ethanol, and then extracted in tetrahydrofuran using a Soxhlet extractor, and dried to obtain a carboxyl microporous polymer.
[0037] Step (2), add 400 mL of N,N-dimethylformamide, 20 g of carboxyl microporous polymer, 11 g of propylene oxide, 38 g of N,N-dicyclohexylcarbodiimide, and 4.4 g of 4-dimethylaminopyridine into a flask, carry out esterification reaction at 35° C. for 18 hours, centrifuge, wash with water and ethanol, then extract in dichloromethane with a Soxhlet extractor, dry, add the product to a 1.2% sulfuric acid solution, carry out hydrolysis reaction at 70° C. for 12 hours, centrifuge, wash with water, and dry to obtain a hydroxyl microporous polymer.
[0038] Step (3), add 1L of 0.25% by mass boric acid aqueous solution and 20g of hydroxyl microporous polymer into a flask, stir and adsorb at 20°C for 6h, filter and wash with water, add the product into a tubular furnace after drying, introduce nitrogen, heat to 850°C, keep warm and calcine for 3h, cool, and obtain a boron-nitrogen co-doped porous carbon material.
[0039] Comparative Example 1
[0040] Step (1), add 1L of 0.06% boric acid aqueous solution and 5g of carboxyl microporous polymer (prepared according to the method of Example 3) into a flask, stir and adsorb at 20°C for 4h, filter and wash with water, add the product into a tubular furnace after drying, introduce nitrogen, heat to 800°C, keep warm and calcine for 4h, cool, and obtain a boron-nitrogen co-doped porous carbon material.
[0041] Comparative Example 2
[0042] Step (1), adding the hydroxyl microporous polymer (prepared according to the method of Example 3) into a tubular furnace, introducing nitrogen, heating to 800° C., calcining at this temperature for 4 h, and cooling to obtain a porous carbon material.
[0043] A fully automatic specific surface area and porosity analyzer was used to conduct nitrogen adsorption and desorption tests on the samples at 77K, draw the adsorption and desorption isotherms, and analyze the specific surface area and pore volume.
[0044] Table 1 Specific surface area and pore volume test
[0045]
[0046] The specific surface area of the boron-nitrogen co-doped porous carbon materials prepared in Examples 3-5 was 1042.7-1506.5 m 2 / g. The total pore volume reaches 0.535-0.883 cm 3 / g. Showing huge specific surface area and pore volume.
[0047] Porous carbon material, acetylene black and polyvinylidene fluoride with a mass ratio of 8:1:1 were added to N-methylpyrrolidone, and the slurry was coated on the surface of copper foil after stirring. After drying, it was cut into electrodes as the negative electrode of lithium-ion batteries. Glass fiber diaphragm was used as battery diaphragm, lithium sheet was used as positive electrode, and solution of ethylene carbonate and dimethyl carbonate containing lithium hexafluorophosphate (concentration 1 mol / L) was used as electrolyte to assemble button cells in an argon glove box. The electrochemical performance of the battery was tested using an electrochemical workstation. The test temperature was 25°C. The current density was 0.1-1A / g. The amplitude was 5 mV / s, and the AC impedance test range was 0.01-100000Hz.
[0048] Table 2 Charge and discharge performance test at current density 0.1 A / g
[0049]
[0050] Table 3 Charge and discharge performance test at current density 1 A / g
[0051]
[0052] It can be seen from the above table that after the porous carbon materials of Examples 3-5 are co-doped with boron and nitrogen, active nitrogen-containing active groups and boron substances are evenly distributed in the porous carbon matrix, there are more electrochemical lithium storage sites, and the specific surface area is large, which can promote the release and embedding of active ions, thereby showing excellent electrochemical performance, high charge and discharge specific capacity, and high coulombic efficiency. Moreover, at a current density of 0.1-1A / g, it also has a high charge and discharge specific capacity and a good rate performance.
[0053] Table 4 Discharge specific capacity performance test at current density 0.1 A / g
[0054]
[0055] Compared with Example 1, the porous carbon of Comparative Example 2 has not been modified by boron doping. The carboxyl microporous polymer of Comparative Example 1 does not contain a polyhydroxy structure, has poor coordination performance with boric acid, and has a weak adsorption effect. A large amount of boric acid is not evenly and effectively adsorbed into the microporous polymer matrix. After calcination, the boron substance is not evenly doped into the porous carbon matrix. The charge and discharge specific capacity and coulomb efficiency of both are low. And after 10 and 100 cycles, the discharge specific capacity decreases at a low rate, and the cycle stability performance is not good.
[0056] The present invention also provides the following technical solutions:
[0057] The porous carbon materials prepared in the above embodiments and comparative examples were used as carriers to prepare phosphorus-carbon composite negative electrode materials, and the preparation process was as follows: 15 g of the porous carbon material obtained above and 30 g of red phosphorus powder were placed together in a quartz tube, and the two materials were spaced apart and placed in parallel; the quartz tube was evacuated and sealed, and then the sealed quartz tube was placed in a tube furnace, heated at 500°C for 8 hours, and then cooled to room temperature to obtain a phosphorus-carbon composite negative electrode material.
[0058] The phosphorus-carbon composite negative electrode material was used as a negative electrode material for a secondary battery to make an electrode, and was applied to a secondary battery for electrochemical performance testing. The electrode preparation process is as follows: the phosphorus-carbon composite negative electrode material, conductive carbon black, and sodium polyacrylate PAANa were added to deionized water in a mass ratio of 8:1:1 and stirred evenly. The obtained slurry was coated on the surface of the copper current collector and dried to make a secondary battery negative electrode. A glass fiber diaphragm was used as a battery diaphragm, a metal sodium sheet was used as a positive electrode, and a solution of ethylene carbonate and dimethyl carbonate containing sodium hexafluorophosphate (concentration 1 mol / L) was used as an electrolyte to assemble a button cell in an argon glove box. The electrochemical performance of the battery was tested using an electrochemical workstation. The test temperature was 25°C. The current density was 0.1-1A / g. The amplitude was 5 mV / s, and the AC impedance test range was 0.01-100000Hz.
[0059] Table 5 Charge and discharge performance test at current density 0.1 A / g
[0060]
[0061] Table 6 Discharge specific capacity performance test at current density 0.1 A / g
[0062]
[0063] Compared with Comparative Examples 1 and 2, in Examples 3-5, the pore structure strength of the porous carbon is greatly improved after boron and nitrogen co-doping, which can well restrain the expansion of the active material during charging; the phosphorus-carbon composite negative electrode material prepared using it as a carrier, when used for the negative electrode of a sodium ion battery, has a high specific capacity retention rate after 100 weeks, reflecting good cycle performance.
[0064] The above-mentioned porous carbon material is used as a carrier to prepare a silicon-carbon composite negative electrode material, and the preparation process is as follows: 50g of the porous carbon material obtained above is placed in a small fluidized bed reactor, and then argon and helium (the volume ratio of argon and helium is 5:1) are simultaneously introduced into the fluidized bed reactor with a flow rate of 2L / h to carry out atmosphere replacement. Then, a mixture of silane and argon is introduced into the fluidized bed reactor at the same time, wherein the mixture of silane and argon (the volume ratio of silane and argon is 8:2) has a flow rate of 4.5 L / h, is heated to 500°C, and is kept warm for 10 hours, so that the silane is cracked to obtain nano-silicon and adsorbed in the porous carbon pores to obtain a silicon-carbon composite negative electrode material; the silicon-carbon composite negative electrode material obtained in the previous step is loaded into a CVD furnace, heated to 950°C, and acetylene with a flow rate of 0.9 L / min, hydrogen with a flow rate of 0.9 L / min, and argon with a flow rate of 1.5 L / min is introduced for a deposition time of 1 hour, so that the acetylene is cracked at high temperature to form pyrolytic carbon coated on the surface of CNT and particles to obtain the final silicon-carbon negative electrode material.
[0065] The silicon-carbon composite negative electrode material is used as a negative electrode material for a secondary battery to make an electrode, and is applied to a secondary battery for electrochemical performance testing. The electrode production process is as follows: the silicon-carbon composite negative electrode material, conductive carbon black, and sodium polyacrylate PAANa are added to deionized water in a mass ratio of 8:1:1, stirred and mixed to obtain a slurry, and coated on the surface of the copper current collector, and dried to make a secondary battery negative electrode. A glass fiber diaphragm is used as a battery diaphragm, a lithium sheet is used as a positive electrode, and a solution of ethylene carbonate and dimethyl carbonate containing lithium hexafluorophosphate (concentration 1 mol / L) is used as an electrolyte to assemble a button cell in an argon glove box. The electrochemical performance of the battery is tested using an electrochemical workstation. The test temperature is 25°C. The current density is 0.1-1A / g. The amplitude is 5mV / s, and the AC impedance test range is 0.01-100000Hz.
[0066] Table 7 Charge and discharge performance test at current density 0.1 A / g
[0067]
[0068] Table 8 Discharge specific capacity performance test at current density 0.1 A / g
[0069]
[0070] Compared with Comparative Examples 1 and 2, in Examples 3-5, the pore structure strength of the porous carbon is greatly improved after boron and nitrogen co-doping, which can well restrain the expansion of the active material during charging; the silicon-carbon composite negative electrode material prepared using it as a carrier, when used in batteries, has a high specific capacity retention rate after 100 weeks, reflecting good cycle performance.
[0071] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a boron-nitrogen co-doped porous carbon material, characterized in that: The preparation method comprises the following steps: Step (1), introducing nitrogen into a flask, adding 1,4-dioxane, pyridine carboxaldehyde intermediate, and 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid, stirring and dissolving, and then dropping acetic acid solution, heating to 100-110° C., condensing and refluxing for 36-48 hours, centrifuging, washing with water and ethanol, and then extracting in tetrahydrofuran with a Soxhlet extractor, and drying to obtain a carboxyl microporous polymer; The structural formula of the pyridine carboxaldehyde intermediate is ; Step (2), adding N,N-dimethylformamide, carboxyl microporous polymer, glycidol, N,N-dicyclohexylcarbodiimide, and 4-dimethylaminopyridine into a flask, carrying out esterification reaction, centrifugation, washing with water and ethanol, and then extracting in dichloromethane using a Soxhlet extractor, drying, adding the product to a sulfuric acid solution, carrying out a hydrolysis reaction, centrifugation, washing with water, and drying to obtain a hydroxyl microporous polymer; Step (3), adding boric acid aqueous solution and hydroxyl microporous polymer to a flask, stirring and adsorbing at 20-35°C for 3-6 hours, filtering and washing with water, adding the product to a tubular furnace after drying, introducing nitrogen, heating to 800-900°C, calcining at this temperature for 2-4 hours, and cooling to obtain a boron-nitrogen co-doped porous carbon material; In the step (2), the esterification reaction is carried out at 20-35° C. for 18-24 hours; and the hydrolysis reaction is carried out at 60-75° C. for 8-12 hours.
2. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 1, characterized in that: In the step (1), the molar ratio of the pyridine carboxaldehyde intermediate to 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid is 1:(1.3-1.7).
3. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 1, characterized in that: The mass fraction of the acetic acid solution in step (1) is ≥80%.
4. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 1, characterized in that: In the step (2), the mass ratio of the carboxyl microporous polymer, glycidol, N,N-dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1:(0.4-0.7):(1.1-2.6):(0.12-0.3).
5. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 1, characterized in that: The mass fraction of the sulfuric acid solution in step (2) is 1-1.6%.
6. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 1, characterized in that: In the step (3), the ratio of the boric acid aqueous solution to the hydroxyl microporous polymer is 1 L: (5-20) g; the mass fraction of the boric acid aqueous solution is 0.06-0.25%.
7. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 2, characterized in that: The preparation method of the pyridine carboxaldehyde intermediate comprises the following steps: introducing nitrogen into a flask, adding toluene solvent, ethanol cosolvent, 5-bromo-2-pyridine carboxaldehyde, 1,3,5-benzenetriboric acid tripinacol ester, and tetrakis(triphenylphosphine)palladium in a molar ratio of (3.3-3.6):1:(0.09-0.12), dropping a potassium carbonate aqueous solution with a molar concentration of 1.5-2 mol / L, heating to 80-100° C., reacting for 18-24 hours, rotary evaporation, adding dichloromethane for extraction, drying the organic phase with anhydrous sodium sulfate, filtering, rotary evaporation, and recrystallizing the product in dichloromethane to obtain the pyridine carboxaldehyde intermediate.
8. The method for preparing a boron-nitrogen co-doped porous carbon material according to claim 7, characterized in that: The volume ratio of the toluene solvent to the ethanol co-solvent is (3-4):
1.
9. Use of the boron-nitrogen co-doped porous carbon material obtained by the preparation method according to any one of claims 1 to 8 in the negative electrode of a lithium / sodium ion battery.
Citation Information
Patent Citations
A method for preparing nitrogen-boron co-doped porous carbon material
CN115140728B
Mesoporous carbon-coated SnO2 nanoflower lithium ion battery negative electrode material and preparation method thereof
CN112701265A
Nitrogen-doped three-dimensional structure porous carbon material as well as preparation method and application thereof
CN117303343A